Fonološki opis govora Dovjega - Škofic, Jožica (Slavia Centralis, 2020)
Phonological description of The Dovje local dialectThe article presents the phonological description of the local dialect of Dovje (SLA T195) in Upper Carniola (Gorenjska). Thus it contains an inventory of phonemes and prosodemes of this dialect, describes their distribution, and the last part is about their origin. This phonological description has been prepared on the basis of dialect recordings from 1967 (the material has been collected with the questionnaire for Slovene Linguistic Atlas), complemented by recordings of dialect discourses from 2013. The local dialect of Dovje is compared with other neighbouring local dialects.
Keywords: phonological description; Gorenjsko/Upper Carniola dialect; Slovene Linguistic Atlas; Dovje